Pengaruh Persepsi Konsumen Terhadap Atribut Produk pada Sikap Terhadap Produk dan Niat Pembelian Ulang : Studi Empirik Pengambilan Keputusan pada Kategori Produk Daging Olahan Beku (The Effect of Consumer Perception on Product Attributes to Attitude Towar - Antofany Yusticia Ahmadi; Suci Paramitasari Syahlani; F. Trisakti Haryadi (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
The objectives of the study were to measure the influence of product attribute perception to attitude toward product, the effect of attitude toward product to repeat purchase intention and to confirm that attitude toward product isa mediating variable between effect in relationship of product attribute perception to repeat purchase intention. One hundred (100) housewives determined by judgmental sampling method were used in the study. The criterion ofrespondent selected was that he/she has a role as food buying decision maker. Data were analyzed by simple and multiple regression analysis. The results indicated that perception on product attribute had significant effect onattitudes toward product and attitude toward product influenced repeat purchase intention. The study showed that 36.5% attitude toward product can be explained by consumer product attribute perception, while 61.6% repeat purchase intention can be explained by attitude toward product. Study also confirmed that attitude toward product attribute was a fully mediating variable relationship of attitude and purchase intention.(Key words: Perception, Attitude, Repeat purchase intention)